Identification of resistance genes effective against rice bacterial blight pathogen in eastern India - Shanti, Marella Lalitha; George, M. L. C.; Cruz, C. M. Vera; Bernardo, M.A.; Nelson, R.J.; Leung, H.; Reddy, J.N.; Sridhar, R. (Scientific Societies, 2001)
Breeding for bacterial blight resistance in rice requires an understanding of the contemporary pathogen populations in the locations where resistance genes are to be deployed. We characterized 450 strains of Xanthomonas oryzae pv. oryzae collected from three states of India using polymerase chain reaction fingerprinting and virulence analysis. This pathogen collection was differentiated into 17 haplotypes (12 lineages at 80% similarity level). Significant differences in the distribution of haplotypes were observed among regions. Virulence analysis of the pathogen collection revealed nine pathotypes. Among the populations from three regions, the Orissa population was the most diverse, consisting of 11 out of 17 haplotypes and five out of nine pathotypes detected in the total collection. Representative pathotypes were used to evaluate seven near-isogenic lines carrying individual bacterial blight resistance genes (Xa3, Xa4, xa5, Xa7, Xa10, xa13, and Xa21) and gene pyramids. Pathogen strains compatible to individual genes were present in detectable frequencies, although no single strain could overcome all resistance genes. Gene combinations Xa4 + xa5, xa5 + Xa21, and Xa4 + xa5 + Xa21 conferred a broad spectrum of resistance to all the strains evaluated, supporting the strategy of pyramiding appropriate resistance genes.